Clinical Features of Primary and Systemic Metastatic Intraocular Lymphomas in Spanish Patients. (16th October 2019) - Llorenç, Victor; Fuster, Carla; Alba-Linero, Carmen; Moll-Udina, Aina; Serrano, Alba; Solé, Manel; Sainz de la Maza, Maite; Aldecoa, Iban; Adán, Alfredo
Abstract : Objectives . To describe and compare clinical findings in different subtypes of biopsy-proven intraocular lymphomas (IOLs). Design . Retrospective, observational case series. Methods . The clinical and pathologic features in IOLs at the Hospital Clinic of Barcelona from 1995 to 2018 were retrospectively studied. Results . Twenty-one patients, 12 men (57%), median age 60 (interquartile range, IQR: 18 years), and a median follow-up of 30 (IQR 60) months were included. Eleven patients had primary vitreo-retinal lymphoma (PVRL, 52%), 4 had primary uveal lymphoma (PUL, 19%), and 6 had systemic metastatic retinal lymphomas (SMRLs, 28%). Diffuse large B-cell lymphoma was the main IOL subset in PVRL (91%) and in SMRL (83%), whereas extranodal marginal zone lymphoma was the only type in PUL (100%). Survival rate was 44% in PVRL and 20% in SMRL at 5 years (p = 0.047 ). One patient had flow cytometry of two different vitreous humour samples. With them, flow cytometry was performed in a total of 11 samples, yielding 7 positive samples. Conclusions and Relevance . Even though PVRL is the most frequent IOL subtype, our findings suggest that PUL and SMRL should be considered as potential IOL causes. Overall survival was poor in PVRL and even shorter in SMRL patients.